2007
DOI: 10.1055/s-2007-984895
|View full text |Cite
|
Sign up to set email alerts
|

Trimethylsilyl Azide (TMSN3): A Versatile Reagent in Organic Synthesis

Abstract: This feature focuses on a reagent chosen by a postgraduate, highlighting the uses and preparation of the reagent in current research Trimethylsilyl Azide (TMSN 3 ): A Versatile Reagent in Organic SynthesisCompiled by Mohammad Jafarzadeh M. Jafarzadeh was born in Babol, Iran. He received his bachelor degree in chemistry from the Islamic Azad University, North Tehran Branch in 1998. He continued his studies in organic chemistry at Kurdistan University, Sanandaj, Iran in 2001, where he investigated the applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 21 publications
0
13
0
Order By: Relevance
“…In addition to the reactions with organic azides, we tested a reaction of 2 with TMS-azide. The TMS group is an easily removable protecting group, and it has been employed as a surrogate for hydrazoic acid . However, instead of isolating the expected imido or tetrazene complex, a reaction of 2 and excess TMS-azide yielded a bis-chromium bridging nitrido complex, [( BMe 2 ,Et TC H )­Cr] 2 (N), 8 , in 50% yield (Scheme ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…In addition to the reactions with organic azides, we tested a reaction of 2 with TMS-azide. The TMS group is an easily removable protecting group, and it has been employed as a surrogate for hydrazoic acid . However, instead of isolating the expected imido or tetrazene complex, a reaction of 2 and excess TMS-azide yielded a bis-chromium bridging nitrido complex, [( BMe 2 ,Et TC H )­Cr] 2 (N), 8 , in 50% yield (Scheme ).…”
Section: Results and Discussionmentioning
confidence: 99%
“…Treatment of 21 with Zn(N 3 ) 2 · 2Py27 or trimethylsilyl azide28 under Mitsunobu conditions did not yield the corresponding azide. Instead, a mixture of elimination product 19 and diisopropyl azodicarboxylate (DIAD) adduct 22 was obtained.…”
Section: Resultsmentioning
confidence: 96%
“…Surprisingly, complex 2 reacted with trimethylsilyl azide (TMSN 3 ) through a different mechanism, producing dimeric complex 3 , which contains ferrocene‐bound 5‐amino‐1 H ‐tetrazol‐1‐yl moieties that are coordinated by their N4 atoms (Scheme ). We assumed that hydrazoic acid was the key reagent in this transformation, resulting from TMSN 3 decomposition …”
Section: Methodsmentioning
confidence: 99%
“…We assumed that hydrazoic acidw as the key reagent in this transformation,r esulting from TMSN 3 decomposition. [6] AlthoughE chavarren and co-workers [7] and Jiao and coworkers [8] have recently reportedf ormally related Au-catalysed TMSN 3 additions across alkynes that produce tetrazoles, analogous reactions with isocyanide substrates have been mostly overlooked. [9] To the best of our knowledge,o nly Yamamoto and co-workersh ave previously reported that TMSN 3 addition to isocyanides gives rise to either cyanamides [10] or 1-substituted 1H-tetrazoles, [11] depending on the catalyst used and on the reactionc onditions (Scheme 2).…”
mentioning
confidence: 99%